When the lights go out... - Bennett, Jules (Bennett, Jules. Angel's Share., 2022)
"Distillery executive Elise Hawthorne always puts business first. No way she'll gamble a lucrative partnership for one night of pleasure. But when a storm outage strands her with VIP client Antonio Rodriguez, he awakens a passion Elise can't ignore. Continuing their clandestine affair when the lights come back on puts everything she's worked for at risk. And now a family secret could blow up her life and cost her the most priceless merger of all..."--